Integrated Heat Regenerator (IHR) Designs with Hydrogen Preheater and Thermoelectric Generator for Power Enhancement of a 2 kW Fuel Cell Vehicle - Mohamed, WANW; Hamdan, Muhammad Hadrami; Zamri, NF; Zakaria, IA; Mohamad, MF; Rosli, MI (International Journal of Integrated Engineering, 2022)
The power train efficiency of fuel cell vehicles (FCV) can be enhanced by improving the hydrogen energy utilization. Based on a mini FCV running on a 2 kW open-cathode Polymer Electrolyte Membrane (PEM) fuel cell, a waste heat recovery system design needs to be developed as an approach towards higher energy efficiency. The novelty of the system is on the integration of thermoelectric generator technology with hydrogen preheating process for a combined heat and power output. This manuscript presents the proposed integrated heat regenerator (IHR) designs, analysed using numerical computational modelling. Three IHR designs were proposed where the main design criteria are (i) a minimum of 10oC hydrogen preheating degree, and (ii) non-parasitic active cooling for the TEG cells. Three design concepts were studied to identify its design and performance limitations. The numerical results were validated with theoretical modelling analysis for hydrogen exit temperatures and TEG surface temperatures. The analysis on predicted fuel cell power enhancement, TEG power generation and waste heat utilization were performed by relating the temperature profiles of the hydrogen reactant and TEG surfaces to fuel cell reaction models and TEG power relationships. A compact IHR design that produced 7.7 to 8 % total power enhancement and suitable in size for a mini FCV was identified for future development works